2005
DOI: 10.1063/1.1935028
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced stress relaxation in ultrathin SiGe-on-insulator by H+-implantation-assisted oxidation

Abstract: SiGe-on-insulator substrate fabricated by melt solidification for a strained-silicon complementary metal-oxide-semiconductor J.Effects of H + implantation ͑ഛ5 ϫ 10 16 cm −2 ͒ on stress relaxation in an oxidation-induced Ge condensation method have been investigated to form stress-relaxed ultrathin ͑ϳ30 nm͒ SiGe-on-insulator ͑SGOI͒ virtual substrates. High-dose ͑ജ10 15 cm −2 ͒ implantation enhanced stress relaxation, which was attributed to bond breaking at the SiGe/ buried SiO 2 interface. However, oxidation v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The effect of ions on a-Si can be understood in terms of their ability to introduce and remove the defect structures necessary for efficient transport of hydrogen through the network. Sadot et al [38] reported stress relaxations of deposited SiGe layers during H + implantation as a result of bond breaking. Ion irradiation stimulated the release of hydrogen implanted in Si from strongly-bonded configurations resulting in diffusion and attachment to vacancy defects [39].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of ions on a-Si can be understood in terms of their ability to introduce and remove the defect structures necessary for efficient transport of hydrogen through the network. Sadot et al [38] reported stress relaxations of deposited SiGe layers during H + implantation as a result of bond breaking. Ion irradiation stimulated the release of hydrogen implanted in Si from strongly-bonded configurations resulting in diffusion and attachment to vacancy defects [39].…”
Section: Introductionmentioning
confidence: 99%
“…However, Sadoh et al [10] reported that implantation of H ions enhanced the oxidation rate, which was caused by the radiation-induced damage. In their experiment, the thickness of surface Si and SiGe layer on SOI is only 85 nm, so the SiO 2 forming during thermal oxidation is not thick enough to prevent the later oxidation of SiGe layer obviously.…”
Section: Composition Analysismentioning
confidence: 98%
“…High temperature oxidation (N1100°C) process is usually used to induce Ge condensation process of SiGe/SOI structures, which is employed to fabricate strained Si on SGOI [4][5][6][7]. On the other hand, low temperature oxidation (b1000°C) process of SiGe has not been clarified yet, even though it is used as isolation process of SiGe devices as reported by Nishisaka et al [8].…”
Section: Introductionmentioning
confidence: 95%